Kualitas kimia,organoleptik, dan aktivitas antioksidan kopi robusta (Coffea canephora) dengan penambahan bubuk daun kelor - Suburi Rahman; Afe Dwiani (Universitas Muhammadiyah Mataram, 2023)
Robusta coffee is a drink that is like by all peoples and has become part of lifestyle. Coffee can be combined with other ingredients to increase its benefits and one of them is moringa. The purpose of this study was to determine the effect of the addition of moringa powder on the quality of robusta coffee. The method that used is this study was complete randomized design (CRD). The treatment of this study was the formulation of coffee and moringa powder with 6 treatments, namely KK0 (100% ground coffee: 0% moringa powder), KK1 (ground coffee 90% : moringa powder 10%), KK2 (ground coffee 80% : moringa powder 20%), KK3 (ground coffee 70% : moringa powder 30%), KK4 (ground coffee 60% : moringa powder 40%) and KK5 (ground coffee 50% : moringa powder 50%). The parameters tested are chemical analysis (moisture content, antioxidant activity and pH) and organoleptic (taste, flavour and color). The results showed that the lowest water content was obtained in the KK0 treatment (3.33%), the highest antioxidant content in the KK5 treatment (87.42%) and the highest pH in the KK0 treatment (6.57). The results for the orgnoleptic test found that the flavour has a value of 2.25 - 3.30 (dislike - neutral) and the taste has a value of 1.95-3.35 (dislike - neutral), while the color has a value of 3.10 - 3.50 (neutral - likes).